A potential role of papaya latex as an anthelmintic against patent ascaridia galli infection in chicken - Endang Purwati Mursof; Simon H (Hemera Zoa, 1991)
The anthelmintic activity of papaya (Carica papaya Linn) latex against patent Ascaridia galli experimental infection with 1000 infectie eggs in chicken was studied. One week after a single dose of papaya latex 20% treatment of infected chicken, their EPG counts decreased. There was a significant, strong positive correlation between the percentage decrease of EPG counts and the single doses of papaya latex 20% given to the birds (r = 0,98; P H 0.05). There was also a very high, negative correlation between adult A. galli numbers recovered from the experimental birds and the single doses of papaya latex 20% (r=0,996; P=0,067). A single dose of 1447.89 mg papaya latex 20% completely freed the birds from A. galli infection while the untreated, infection controls harboured a mean number of 50 adult worms. The 100% effective dose (ED100) of papaya latex 20% per bird. The egg and body weights of treated, infected chicken improved to become similar to those of the untreated, unifected controls.